Self-concept a conceptual and methodological study in the Philippine context - Pasao, Myrna M. (1979., 1979)
The development of a self-concept rating scale was the focus of this study. The subjects were students from eight selected schools in Metro Manila. The conceptual scheme that guided the research was inspired by Rogers' Self-Theory and the Theory of Interpersonal Relationship of Sullivan. The results of the study showed that there were ten psychosocial factors which can be considered significant in assessing the self-concept of urban high school students, four of which seem to be indicative of the Filipino self. Based on the aforementioned findings, the self-concept ratings scale may in some degree be safely used as one of the tools for counseling in an urban secondary school in the Philippines.
Mimeographed.
Thesis (Ed.D)--University of the Philippines, Diliman.
Keywords: Self-perception.